Briswalk with IPSis: what it takes to be the biggest loser - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
The What It Takes to be The Biggest Loser IPSis program was held from 8 until 14 February 2023 through a screening of health examinations for all IPSis staff. A total of 18 IPSis staff members participated in the Briskwalk 2.0 program before the month of Ramadan arrived. The route used for the Briswalk 2.0 is using the road around UiTM. A healthy lifestyle through productive physical activity such as brisk walk can help make people more active and have a healthier lifestyle.